2009
DOI: 10.1515/mamm.2009.072
|View full text |Cite
|
Sign up to set email alerts
|

Use of photographic capture-recapture sampling to estimate density of Striped Hyena (Hyaena hyaena): implications for conservation

Abstract: No abstract available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…Photographic capture recapture has been used for estimating densities of many secretive large carnivore species, including tigers [34], [43], [44], leopards [27], [38], [44], snow leopards ( Panthera uncia) [45], jaguars ( Panthera onca) [46] and hyaenas [47]–[49]. The previous conventional analyses of obtaining population density have given way to more robust methods that use the spatial information of location of traps rather than methods that estimate the size of the effective area heurestically [35], [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photographic capture recapture has been used for estimating densities of many secretive large carnivore species, including tigers [34], [43], [44], leopards [27], [38], [44], snow leopards ( Panthera uncia) [45], jaguars ( Panthera onca) [46] and hyaenas [47]–[49]. The previous conventional analyses of obtaining population density have given way to more robust methods that use the spatial information of location of traps rather than methods that estimate the size of the effective area heurestically [35], [41].…”
Section: Discussionmentioning
confidence: 99%
“…Harihar et al [44] found that the density of leopards in the Rajaji National Park decreased from 9.76/100 km 2 to 2.07/100 km 2 with a concurrent increase of tiger populations following relocation of people from within the Park. Recent estimates from camera trapping studies on hyaenas outside protected areas in India report density of 3.67–6.5/100 km 2 [48] whereas higher densities of 15.1/100 km 2 [47] and 3.9–5.67/100 km 2 [49] were obtained from within the protected areas of Sariska Tiger Reserve and Rajaji National Park, India.…”
Section: Discussionmentioning
confidence: 99%
“…A total of seven dens of Striped Hyaena (two abandoned) were recorded in the areas, which were close to riparian corridors. Harihar et al (2010) recorded six to eight individuals of Striped Hyena in the Chilla forest.…”
Section: Joshi | Mammals Of Rajaji National Park Indiamentioning
confidence: 99%
“…They are known to occur across most of India, including the wet forests of southwestern India, except northeastern India (Reiger 1979). Several studies have discussed their occurrence and abundance within and near protected areas, such as Kumbalgarh and Esrana (Singh et al 2010), Rajaji National Park (Harihar et al 2010), Sariska Tiger Reserve (Gupta et al 2009) and Gir National Park ). Yet Striped Hyenas are known to be tolerant of human habitation, occurring in human-dominated landscapes in western India (Singh et al 2010).…”
mentioning
confidence: 99%